DEVELOPMENT OF TEACHER COMPETENCIES IN DRIVING SCHOOLS - Chandra S. Haratua; Muaidin Muaidin; Abdul Goni; Holilah Rahmawati; Cahyono Kuntorojati (Jurnal Scientia, 2023)
The Covid-19 pandemic prompted the government to reform the "2013 Curriculum" into the "Independent Curriculum". Schools and teachers are key Independent Curriculum actors that focus on the Pancasila student profile. This research aims to determine the development of teacher competency and teacher efforts in developing their competency at the Driving School. Qualitative descriptive methods were used in this research. The research was conducted at Nurul Hikmah Al Hakim Middle School. The sampling technique used was purposive sampling. Data was collected through observation and discussion with 15 subject teachers. The interview process was semi-structured by providing a form, and then the data results were analyzed by reducing and drawing conclusions. This research indicates that driving schools are trying to develop learning activities for students towards the Pancasila Student Profile. The development is the teacher's ability to innovate in teaching modules and the Pancasila Student Profile Strengthening Project Module. Teachers' concerns about short-duration online training activities can be overcome with learning community activities so that teacher competency development can reach targets.